2014
DOI: 10.1002/adom.201400350
|View full text |Cite
|
Sign up to set email alerts
|

Finely Tuned Blue Iridium Complexes with Varying Horizontal Emission Dipole Ratios and Quantum Yields for Phosphorescent Organic Light‐Emitting Diodes

Abstract: Two new heteroleptic blue emitting Ir(III) complexes, EtOCN-FIracac and tBuCN-FIracac, and a homoleptic Ir(III) complex, tBu-FCNIr, consisting of 2′,4″-difl uorophenylpyridine (dfppy) with a cyano (CN) group at the 5′ position of the phenyl and an ethoxy (EtO-) or tert -butyl (tBu) group at the 4 position of the pyridine as the main ligands, are synthesized and characterized for phosphorescent organic light-emitting diodes (PhOLEDs). The dual functionalization of the dfppy core with the electron-withdrawing CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Angle-dependent p-polarized emission measurements of doped films by photoluminescent excitation are used to determine the net orientation of the TDVs of emissive dopants 4,12,23,25,[36][37][38] . We define the value Θ as the ratio of power radiated by vertical components of the contributing TDVs to the total power radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Angle-dependent p-polarized emission measurements of doped films by photoluminescent excitation are used to determine the net orientation of the TDVs of emissive dopants 4,12,23,25,[36][37][38] . We define the value Θ as the ratio of power radiated by vertical components of the contributing TDVs to the total power radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Heteroleptic complexes of the formula (C ∧ N) 2 Ir(O ∧ O), where C ∧ N is a cyclometalated ligand and O ∧ O is a diketonate ligand such as acetylacetonate (acac), have previously been observed to demonstrate higher EQEs than their homoleptic Ir(C ∧ N) 3 analogues, because their average TDVs are disproportionately horizontal relative to the substrate in solid films 11,[16][17][18][19][20][21][22][23][24][25] . There are numerous reports of other dopants with ancillary ligands, especially acac and its close analogues, which feature net parallel TDV orientations to various degrees in doped films (see Supplementary Table 1 for tabulated literature data) [22][23][24][25] .…”
mentioning
confidence: 99%
“…Thereafter, the search began for other iridium complexes exhibiting nonisotropic alignment of their TDMVs. As a consequence, several other molecules were found to display behavior similar to IrðmdqÞ 2 ðacacÞ, and the importance to light outcoupling was demonstrated [81,86,87,[209][210][211][212][213][214][215][216][217][218]. Using the feature of predominantly horizontal alignment of the TDMVs of such Ir complexes subsequently allowed OLED efficiencies for direct…”
Section: Iridium Complexes Exhibiting Deviations From Isotropymentioning
confidence: 99%
“…21 Several examples of these groups include: trifluoromethyl, 22 sulfonyl, 23 phosphonium, 24 diarylphosphine oxide 23b and nitrile. 21,25 In addition, there have also been efforts to change the aryl ring of the C^N ligands altogether from phenyl to a heterocycle such as pyridine, 26 pyridinium 27 or even pyrimidine. 28 The nitrogen atoms in these heterocycles stabilise the HOMO by inductively withdrawing electron density away from the metal centre ( Figure 5).…”
Section: : C^n Ligand -Effects Of Substitution On the Phenyl Ringmentioning
confidence: 99%
“…explored. An early example of the use of methoxy groups to mesomerically red-shift emission was reported by Watts et al, 34 who showed that the emission of the triscyclometalated complex fac-[Ir(ppy) 3 ] (24) could be red-shifted if -OMe groups were appended para to the Ir-C bond (25) or blue-shifted if they were in a meta relationship 26 Our study explored decoration of the C^N ligands with an increasing number of -OMe groups in a systematic fashion to red-shift the emission and explore the competing σwithdrawing effects with the π-donating effects of these substituents (29a -32b). 36 The electrochemistry follows the trend found for the emission properties.…”
Section: : C^n Ligand -Effects Of Substitution On the Phenyl Ringmentioning
confidence: 99%